Challenges in adolescent health care offered by primary health care - Darine Marie Rodrigues da Silva; Diogo Timoteo Costa; Jael Maria de Aquino; Flávia Maria Barros Lavra; Julieth Merelis Rodrigues da Silva; Tereza Natália Bezerra de Lima; Mailla Morena Costa e Silva (Universidade de Pernambuco, 2021)
Objective: to demonstrate the factors that pose challenges in the integral health care of adolescents offered by primary health care. Method: This is an integrative literature review study carried out in four databases. On these bases, three descriptors identified in the DECS were crossed, such as: adolescent, primary health care and comprehensive health care. To search for the articles, the combination of the three descriptors was performed with the Boolean operator "AND". Results: At the end of the show, they included 8 articles published in national newspapers, and various challenges were identified. Among them, two professionals will stand out due to the lack of training for the assistance of adolescents and the blaming of adolescents for all the mistakes they have given. Conclusions: There was a clear need for the optimization of health care provided to adolescents by primary health care services.